2012
DOI: 10.1002/uog.10053
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant right subclavian artery: incidence and correlation with other markers of Down syndrome in second‐trimester fetuses

Abstract: Objective To assess the incidence of aberrant right subclavian artery (ARSA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 20 publications
5
84
0
1
Order By: Relevance
“…Several authors recommended karyotyping even if ARSA is the only positive marker [5,11], while it has been claimed that ARSA without another sonographic finding is not a powerful enough argument to recommend karyotyping [12]. In three previous series there was no case of trisomy 21 with isolated ARSA [4,6,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors recommended karyotyping even if ARSA is the only positive marker [5,11], while it has been claimed that ARSA without another sonographic finding is not a powerful enough argument to recommend karyotyping [12]. In three previous series there was no case of trisomy 21 with isolated ARSA [4,6,12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the series with 8 fetuses with ARSA and Down syndrome, Borenstein et al [5] reported that only 1 fetus (12.5%) had ARSA as an isolated finding. Recently, Paladini et al [11] reported a series of 27 fetuses with ARSA and Down syndrome, and ARSA was isolated finding in 8 (29.6%) of them. In the same study, the authors drew the conclusion that ARSA should be considered among the three most powerful ultrasound indicators of Down syndrome in second trimester, together with nasal bone hypoplasia/absence and increased nuchal fold [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the postnatal period, and most recently also in the prenatal period, ARSA was found significantly more often in subjects with congenital heart disease (CHD) [8] or chromosomal abnormalities, particularly trisomy 21 [9,10,11], with the relative risk multiplied by 3.94 [12]. …”
Section: Introductionmentioning
confidence: 99%